96-week results of a dual therapy with darunavir/ritonavir plus rilpivirine once a day vs triple therapy in patients with suppressed viraemia: virological success and non-HIV related morbidity evaluation. Issue 1 (2nd January 2020) - Di Cristo, Valentina; Adorni, Fulvio; Maserati, Renato; Annovazzi Lodi, Marco; Bruno, Giuseppe; Maggi, Paolo; Volpe, Anna; Vitiello, Paola; Abeli, Clara; Bonora, Stefano; Ferrara, Micol; Cossu, Maria Vittoria; et al.
Abstract : Antiretroviral therapies have been tested with the goal of maintaining virological suppression with a particular attention in limiting drug-related toxicity. With this aim we designed the DUAL study: a randomized, open-label, multicenter, 96 weeks-long pilot exploratory study in virologically suppressed HIV-1+ patients with the aim of evaluating the immunovirological success and the impact on non-HIV related morbidity of switching to a dual therapy with darunavir-ritonavir (DRV/r) and rilpivirine (RPV). We recruited patients who received a PI/r-containing HAART for ≥6 months, HIV-RNA < 50 cp/mL for ≥3 months, eGFR > 60 mL/min/1, 73m2, without DRV or RPV RAMs. We randomized patients in arm A: RPV + DRV/r QD or arm B: ongoing triple therapy. The primary endpoint has been defined as the percentage of patients with HIV-RNA < 50 cp/mL at week 48 (ITT). VACS index, Framingham CVD risk (FRS) and urinary RBP (uRBP) were calculated. We used Chi-square or Fisher statistics for categorical variables and Mann-Whitney U for continuous ones. Forty-one patients were enrolled (22 in arm A, 14 in arm B, plus 5 screening failures): 30 patients reached 96 weeks: 100% had HIV-RNA < 50 cp/mL in arm A versus 91.7% in arm B. Similar changes were observed in median CD4/mL between baseline and week 96 (+59 versus − 31, p: n.s.). Thirty-one in arm A and 23 in arm B adverse events took place, whereas only 1 was serious (arm A: turbinate hypertrophy, unrelated to HAART). Among the 6 discontinuations (3 in A, 3 in B), only 1 was related to adverse event (arm A: G3 depression, insomnia, weakness). VACS index, median FRS and median uRBP values did not vary from baseline to week 96. At 96-weeks all patients switched to a QD 2-drug regimen based on DRV/r + RPV maintained HIV-RNA suppression, but a single patient who showed a virological failure at week 4. CD4 counts increased overtime without significant differences between the two arms. The novel dual regimen was well tolerated with the same amount of discontinuation as the control arm. VACS index, FRS and uRBP did not differ between arms at week 96.